Meeting report of the 7th Heidelberg Myeloma Workshop: today and tomorrow - Bärtsch, Marc-Andrea; Lutz, Raphael; Raab, Marc-Steffen; Weinhold, Niels; Goldschmidt, Hartmut (Journal of cancer research and clinical oncology, 2019)
PURPOSE: The 7th Heidelberg Myeloma Workshop was held on April 5th and 6th, 2019 at the University Hospital Heidelberg. - METHODS AND RESULTS: Main topics of the meeting were (1) diagnostics and prognostic factors, (2) role of immunotherapy in multiple myeloma (MM), (3) current therapy of MM, (4) biology and genomics of MM as well as (5) novel treatment concepts. A debate on the status of minimal residual disease (MRD) driven therapy was held. - CONCLUSION: Diagnostics and treatment of newly diagnosed and relapsed MM are continuously evolving. While advances in the field of (single cell) genetic analysis now allow for characterization of the disease at an unprecedented resolution, immunotherapeutic approaches and MRD testing are at the forefront of the current clinical trial landscape.